In-vitro cell interaction and apatite forming ability in simulated body fluid of ICIE16 and 13-93 bioactive glass coatings deposited by an emerging suspension high velocity oxy fuel (SHVOF) thermal spray - Bano, S.; Romero, A. Rincon; Grant, D.M.; Nommeots-Nomm, A.; Scotchford, C.; Ahmed, I.; Hussain, T. (Surface and Coatings Technology, 2021)
ICIE16 and 13-93 bioactive glasses have been proposed as alternative chemically stable compositions in physiological fluid keeping bioactivity comparable to Bioglass®. ICIE16 and 13-93 bioactive glasses coatings were produced via an emerging suspension high-velocity oxy-fuel (SHVOF) thermal spraying technique. Suspensions of ICIE16 and 13-93 with 10 wt% solid loading in isopropanol (IPA) and water were used to produce coatings on AISI304 stainless steel using a flame power of 50 kW and 75 kW. For both glass formulations, the coatings deposited at a lower flame power were more porous, less hard, and less rough ( 6% porous and 242 HV) than the coatings obtained at a higher flame power ( 4% porosity and 300 HV). ICIE16 coatings showed more dissolution in SBF (simulated body fluid) than the 13-93 coatings. Moreover, the 13-93 glass coating sprayed at 75 kW showed the highest stability in SBF since only 2% of the coating was resorbed in SBF after 7 days of immersion and revealed apatite precipitation after 7 days. In-vitro cell tests, using MG63 cells, showed good cell attachment and proliferation on the surfaces of the coatings, revealing good cytocompatibility. The 13-93 coating sprayed at 75 kW revealed the highest cell proliferation after 7 days of incubation. This can be attributed to the higher surface roughness of the coating (Ra = 6.5 ± 0.6 μm).
Keywords: Materials Chemistry; General Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics